Community Participation to Prevent Theft of Two-Wheeled Motor Vehicles by the Bogor Police Binmas Unit - Jevo Batara (Advances in Police Science Research Journal, 2020)
The high number of cases of theft of motorized 2-wheeled vehicles in the Bogor Police jurisdiction in the 2016-2019 period is inseparable from the performance of the Bogor Polres Binmas Unit in building Community Participation to be with the National Police in overcoming the social phenomenon. The Police Pre-emptive approach that has been carried out by Bhabinkamtibmas through counseling methods through face-to-face meetings at the Village Hall, in the Mosques, through the village sambang and door to door visits, and Focus Group Discussion (FGS) is addressed by the community with an attitude of "indifferent indifferent "because it was felt to only take up precious time, burden the finances, and even put people at risk of safety. Free, not time-consuming, easy, and no risk is a condition that needs to be considered by the Bogor Police Resort Binmas Unit and its Bhabinkamtibmas staff in determining communication methods so that community development efforts can be more effective and efficient in order to foster community participation to assist the police mission in combating crime, especially the 2-wheel chans. The development of social patterns and patterns of community life in the Bogor Police jurisdiction as an Urban Community that is highly dependent on social media in communicating with each other, is an opportunity that can be utilized by the Bogor Police Binmas Unit especially its Bhabinkamtibmas by forming "WhatsApp" groups with members all walks of life of the target people. Providing mutual information through WhatsApp groups is expected to overcome obstacles that have been experienced, both by Bhabinkamtibmas and the Community in the context of tackling 2-wheel chansmor in the future.Keyword : Effort and Factor binluh, drugs abusing.